2022
DOI: 10.24014/juring.v5i2.14933
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical Learning Trajectory Sistem Persamaan Linear Dua Variabel Berbasis Realistic Mathematics Education

Abstract: Tujuan dari penelitian ini adalah untuk mengasilkan lintasan belajar/ HLT Sistem Persamaan Linear Dua Variabel (SPLDV) dengan pendekatan Realistic Mathematics Education (RME). Penelitian ini menggunakan metode desain research yang terdiri dari 3 tahap yaitu, yaitu preparing for the experiment, design experiment, dan retrospective analysis. Pengumpulan data dilakukan dengan dokumentasi dan wawancara. Teknik analisis data dalam penelitian ini yaitu mereduksi data, penyajian data, dan penarikan kesimpulan. Subjek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Based on the results of interviews with principals, science teachers, and students at UPT SMP Negeri 12 Medan, found that in the learning activities of students, teachers are more dominant in providing theory, more concerned with memorization and solving physics problems, and science teachers are more likely to use the lecture method. According to (Hidayati, 2022) "the lecture method is oral explanation and narration by the teacher in front of students and in front of the class, especially with the character of self centered and instantaneous students affecting their learning discipline and response during learning". Teachers do not maximally use learning media when delivering subject matter and only explain the material, so that students are less active because they are only limited to seeing, hearing and taking notes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of interviews with principals, science teachers, and students at UPT SMP Negeri 12 Medan, found that in the learning activities of students, teachers are more dominant in providing theory, more concerned with memorization and solving physics problems, and science teachers are more likely to use the lecture method. According to (Hidayati, 2022) "the lecture method is oral explanation and narration by the teacher in front of students and in front of the class, especially with the character of self centered and instantaneous students affecting their learning discipline and response during learning". Teachers do not maximally use learning media when delivering subject matter and only explain the material, so that students are less active because they are only limited to seeing, hearing and taking notes.…”
Section: Introductionmentioning
confidence: 99%